Strategi Pengembangan Pondok Pesantren Al-Mu’awanah dalam Meningkatkan Kreativitas Santri - Nurholisoh Nurholisoh (Jurusan Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2018)
The purpose of this study was to determine the ability of cottage management in increasing the creativity of santri, to find out the motivations and programs available at the boarding of Al-Mu'awanah Islamic boarding school in increasing the creativity of santri. The method used in this study is descriptive method, because the purpose of this study is to describe and provide an explanation of the development strategy in Al-Mu'awanah in increasing students' creativity. The steps taken in the research are determining the location of research, research methods, data types, data sources, data collection techniques, and finally analyzing. The results of this study indicate that the manager of Al-Mu'awanah boarding school is able to increase the creativity of his santri. Motivation given by giving rewards, punishing the violating santri, provide facilities and holding various activities programs to increase the creativity of santri boarded by Al-Mu’awanah Islamic boarding school.